Assessment of the Farmers’ Use of Ict Tools in Farming Practices - Ghosh, Mithun Kumar; Rafi, S. M.; Mahmud, Iqbal Hasan; Turin, Mursaleen Zebin (European Journal of Applied Sciences, 2022)
It has been two decades into the current century which is marked by the revolutionary development and expansion of Information and Communication Technology (ICT), especially across the socioeconomic structure in the underdeveloped and developing countries. The emerging practices of integrating ICT facilities in agricultural sector has shown to be quite promising. This study was designed to determine the use of ICT as an extension tool by farmers in Diyar region (four villages) of Chapainawabganj district, Bangladesh. In this particular area, with many shortcomings, traditional public extension services have been prevalent. The use of ICT as dynamic agricultural extension tool has the potential to fill in the voids left by the traditional extension services. The research work presented in this paper studied the socio-demographic characteristics of the famers, extent of use of ICT tools by the farmers and the attitude of the farmers towards ICT use. Most of the respondents had shown moderately favourable attitude. Education, land ownership and cosmopoliteness showed positive significant relationship. And age, family member, number of children and farming experience showed negative significant relationship with the attitude of the farmers towards using ICT tools. Some basic resistances such as need for availability, accessibility, knowledge, interest and some others are keeping the growth of ICT usage low among the farmers of the chosen area. Evidently more work needs to be done to reach the expected rate of ICT led solutions for the promising agriculture in Chapainawabganj.